Factor structure of the Chinese version of Emotion Regulation Goals Scale - Chen, Shengdong; Chi, Cheng; Luo, Li; Zhu, Weiwei; Chen, Yi; Wang, Tao; Yuan, Jiajin (Frontiers in Psychology, 2024)
Recent studies in Western cultures suggested emotion regulation goals have important implications for mental health. This study aimed to test the factor structure of Emotion Regulation Goals Scale (ERGS) in a Chinese cultural context. Exploratory factor analysis (EFA) and Confirmatory factor analysis (CFA) were first used to examine the factor structure of the ERGS, and then reliability and validity tests were conducted to examine the psychometric properties of the ERGS. Results showed that the original five-factor model demonstrated fit during both EFA and CFA, and was thus adopted for further psychometric analyses. Most of the five factors were significantly associated with emotion regulation tendencies and negative emotional outcomes (e.g., depression), except for the non-significant associations between pro-hedonic goals and expressive suppression, and pro-social and impression management goals with depression. The ERGS also showed good internal consistency and split-half reliability. However, the test-retest reliabilities varied substantially across the five factors. The pro-hedonic goal had a higher test-retest reliability, whereas the contra-hedonic, performance, pro-social, and impression management goals showed lower values, especially the latter two. In brief, the ERGS showed a promising five-factor structure in assessing emotion regulation goals in Chinese cultural context.